End‐to‐end anastomosis of the common bile duct and cholecystoduodenostomy for the treatment of extrahepatic cholangiocarcinoma in an 11‐year‐old cat. Issue 4 (24th July 2021) - Jifcovici, Alexandra; Caraty, Johan; Vincken, Gaëlle; Bongartz, Alexandre
Abstract: An 11‐year‐old cat presented with a 10‐day history of anorexia and jaundice. Diagnostic examinations showed hyperbilirubinemia, dilatation of the bile ducts and a mural mass in the common bile duct. Cholecystoduodenostomy, mass resection and end‐to‐end anastomosis of the common bile duct were performed. Histopathology revealed a well‐differentiated cholangiocarcinoma. The cat improved clinically and had a good quality of life for 16 months prior to disease recurrence. Liver biopsy indicated metastasis of the primary tumour. Euthanasia was elected. Cholangiocarcinoma in cats is considered to have a poor prognosis with high rate of metastasis. Given the paucity of information in the veterinary literature and the lack of specific prognostic indicators, guidelines for feline cholangiocarcinoma management have not been fully established. This clinical case report describes an acceptable outcome after tumour resection and biliary diversion in an 11‐year‐old cat with extrahepatic cholangiocarcinoma and no pre‐existing metastases.